2018
DOI: 10.4102/phcfm.v10i1.1660
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in primary care: Integration through in-service training in a South African rural clinic

Abstract: BackgroundIntegrating mental health into primary care is a global priority. It is proposed to ‘task-share’ the screening, diagnosis and treatment of common mental disorders from specialists to primary care workers. Key to facilitating this is training primary care workers to deliver mental health care. Mental health training in Africa shows a predominance of short-term, externally driven training programmes. Locally, a more sustainable delivery system was needed.AimThe aim of the study was to develop and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Improving mental health literacy among other staff through awareness campaigns that address the impact of untreated CMDs and the benefits of mental health counselling may also help create a facility climate conducive to counselling implementation. Practical steps forward could include inservice staff training around mental health issues (Maconick et al 2018), mental health awareness drives, and integrating mental health promotion initiatives into workplace policies (Petersen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Improving mental health literacy among other staff through awareness campaigns that address the impact of untreated CMDs and the benefits of mental health counselling may also help create a facility climate conducive to counselling implementation. Practical steps forward could include inservice staff training around mental health issues (Maconick et al 2018), mental health awareness drives, and integrating mental health promotion initiatives into workplace policies (Petersen et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Such perceptions also affect the confidence levels of health care professionals as well as their productivity. In order to improve the situation, the implementation of the proposed programme could be effected through in-service training and health care professionals engaged in continuous education-development programmes (Maconick et al, 2018), as this low perception level may not be unconnected with their level of education. Research has shown that health care professionals demonstrated poor skills in the diagnosis of mental disorders due to their lack of training and awareness.…”
Section: Discussionmentioning
confidence: 99%
“…The perception of health workers about the treatment of comorbid mental health conditions and HIV infection can be boosted through the adoption of a pragmatic model that can be sustained in the long run. Such a model should address the educational needs of the health care professionals and their negative mind-set and fears about the integration of mental health into HIV services at the primary health care level (Maconick et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…• As a result, the vision of the South African Government has not been met (Table 1)not helped by the lack of investment in communitybased psychiatric and psychosocial rehabilitative services in recent years to support de-institutionalization of services. However, this may change with greater integration of mental health services in primary care and greater task-sharing [36,220,224,225]. The lack of investment was highlighted by the number of deaths of mentally ill patients in Gauteng Province following the instigation of the National Mental Health Policy Framework [226].…”
Section: South Africamentioning
confidence: 99%